Stability of the viscoelastic Mises truss = Stateczność lepkosprężystej kratownicy Misesa - Marcinowski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A nonlinear equilibrium equation of Mises truss was derived in the paper. It was differential equation with respect to time due to the fact that the material from which the rods were made was viscoelastic. The six parameter rheological model was used for this material. These parameters were identified in creep bending test. The identified parameters were used in numerical example inserted in the paper. In this example the critical times for various levels of load were calculated. The differential equation was solved by means of numerical procedure NDSolve from the Mathematica? packet.
Keywords: lekkosprężystość; stateczność; kratownica Misesa; czas krytyczny; viscoelasticity; truss stability; critical time; creep bending test